Between the Mediatic and the Mediumistic: Haunted Media in Contemporary Horror Cinema - Bruno Surace (Cinergie)
The paper examines the interplay between media and the supernatural in contemporary horror cinema, focusing on the concept of haunted media—communication technologies that become conduits for metaphysical malevolence. Drawing from the theoretical frameworks of Jeffrey Sconce’s media hauntology and Jacques Derrida’s hauntology, it explores how films reflect societal anxieties surrounding technology and its “magical” qualities. The analysis delves into the moral panic and techno-fetishism inherent in media history, emphasizing how communication tools blur the lines between the mediatic and the mediumistic. Four case studies are analyzed: Truth or Dare (Jeff Wadlow, 2018) portrays a demon that spreads its curse through media, highlighting moral panic around teen culture; Countdown (Justin Dec, 2019) investigates smartphone dependency and algorithmic determinism; Friend Request (Simon Verhoeven, 2016) explores digital connectivity as both a social enabler and a source of isolation through ghosting and stalking; and Cam (Daniel Goldhaber, 2018) examines identity fragmentation in the age of digital reproduction and surveillance. These films, though largely genre-based, serve as mirrors of the current mediascape, where technological advances evoke both fascination and dread. They reveal the ethical and gendered dimensions of media-induced fears, situating horror cinema as a laboratory for cultural anxieties and social critique.